Peningkatan Kemampuan Pengenalan Sejarah Budaya Minangkabau Melalui Lagu Kreasi Minangkabau Bagi Anak Usia Dini - Vivi Anggraini; Adi Priyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to describe the process and learning outcomes of Minangkabau creation songs to stimulate the introduction of the history of Minangkabau culture for children in kindergarten aged 5-6 years. This study uses action research in group B in TK Nurul Hidayah, West Sumatra. The method used is the Kemmis and Taggart method which consists of planning, action, observation, and reflection. Data collection techniques used were observation, interviews, field notes, action monitoring instruments and documentation. Data analysis is presented quantitatively and qualitatively. The results of quantitative data show that the ability to recognize children's history can increase after action is taken through Minangkabau creation songs. This can be seen from the results of the study which stated that the class average at pre-action was 54%. After the action in the first cycle, the class average increased to 69.70% and the second cycle increased by 82.74%. From the results of this study, it can be concluded that Minangkabau creation songs are able to increase the ability to recognize the historical history of the Minangkabau region. Keywords: History of Minangkabau Culture and Minangkabau Creation Songs